KOORDINASI DAN TANTANGAN IMPLEMENTASI PROGRAM MAKAN BERGIZI GRATIS (MBG) ANAK SEKOLAH MELALUI PELIBATAN UMKM PEREMPUAN DI BOGOR - Renea Shinta Aminda; Indupurnahayu; Trisno Nugroho (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2025)
This study aims to analyze the implementation of the Free Nutritious Meals (MBG) program in Bogor City, with a specific focus on involvement of women-led micro, small, and and medium enterprises (MSMEs). The study employed a mixed methods approach with a parallel convergent design. The research was conducted in Bogor City, Indonesia, with data collection carried out between July and September 2025. Primary data were obtained through in-depth interviews with three key institutions: the Education Office, the Cooperatives and MSMEs Office, and the Asperbang (Indonesian Agency for the Development of Women's Empowerment and Development), complemented by a survey of 16 women-owned MSMEs in the food sector in Bogor. Secondary data were obtained from official government reports on program beneficiaries and MSME databases. Quantitative data were analyzed using descriptive statistics, while qualitative data were used to identify coordination mechanisms, institutional gaps, and barriers to MSME participation. The research findings reveal a significant gap between policy design and implementation of the MBG program. Although the program aimed to involve women-owned MSMEs, its implementation was largely centralized under national-level authorities, with no clear standard operating procedures (SOPs), limited integrated data, restricted information access, and weak cross-agency coordination. As a result, most women-owned MSMEs were unaware of participation pathways despite strong interest, indicating that limited involvement stemmed from institutional design constraints rather than capacity limitations.